METODE PEMBELAJARAN GUIDED DISCOVERY TERHADAP KEMAMPUAN MENGENAL KONSEP WARNA PADA ANAK AUTIS - SAIFOUR FAROCHI, M. (Jurnal Pendidikan Khusus, 2016)
ABSTRACT This research was formed background the importance of developing recognizing color concept ability to early age autism children. Based on the observation in the field about recognizing color concept ability, one of the basic color and secondary color possessed by the autism children in TK Putra Harapan still needed to be developed. It appeared to the children’s ability in mentioning, showing basic color and secondary color still low. The recognizing color concept ability of autism children in this research was developed through guided discovery learning method which the children were actively stimulated through the direct involvement by engaging the learners’ ability optimally to search and find with the learning material of recognizing color concept through the mental process itself. This research had purpose to prove the influence of guided discovery learning method toward recognizing color concept ability to autism children in TK Putra Harapan Sidoarjo. This research method used quantitative approach, with pre-experimental kind, and one-group pretest—posttest design.  The sample in this research was Group B autism children in TK Putra Harapan Sidoarjo, 6 children whose recognizing color concept ability still needed to be developed. The data collection technique in this research used observation and documentation. The data analysis technique used statistik non parametik with wilcoxon Match Pairs Test.    The research result indicated that there was influence of guided discovery learning method toward recognizing color concept ability of autism children in TK Putra Harapan Sidoarjo. It was seen from the research result that indicated T counted = 0 was smaller than T table = 2 with significant level 5% which meant that there was influence of guided discovery learning method toward recognizing color concept ability of autism children in TK Putra Harapan Sidoarjo.   Keywords:  Color Concept, Guided Discovery